Hubungan antara Grit dengan Regulasi Diri Dalam Belajar pada Siswa Kelas XII SMA Negeri - Araz Arza Zera Wijaya; munawir yusuf; Afia Fitriani (UNS Press, 2022)
Senior high school requires students to have harmonization of their abilities and needs in the world of work, which is manifested in the choice of the right lecture majors. Students with low self-regulation in learning tend to show absence or low participation in class during the learning process. Self-regulation in learning is closely related to grit, namely the tendency to direct and maintain perseverance and interest in the long term. The purpose of this study was to reveal the correlation between grit and self-regulation in learning. The population of this research is the XII grade students of SMA Negeri